The murder of the century [compact disc, unabridged] : the gilded age crime that scandalized a city & sparked the tabloid wars - Collins, Paul, 1969- (AudioGO, 2011)
In Long Island, a farmer found a duck pond turned red with blood. On the Lower East Side, two boys playing at a pier discovered a floating human torso wrapped tightly in oilcloth. Blueberry pickers near Harlem stumbled upon neatly severed limbs in an overgrown ditch. The grisly finds that began on the afternoon of June 26, 1897, plunged detectives headlong into the era's most perplexing murder.